2001
DOI: 10.1002/cjce.5450790126
|View full text |Cite
|
Sign up to set email alerts
|

On the determination of diffusivities of volatile hydrocarbons in semi‐solid bitumen

Abstract: Residual volatile hydrocarbons in bitumen constitute a potential source of air pollution. Diffusivities of volatile components in bitumen are needed to assess the extent of environmental damages that could result from bitumen spill or working loss of vapour to the atmosphere. Knowledge of solvent dispersion is also required in the recovery of viscous bitumen by solvent displacement. This paper discussed the de‐coupled transfer model developed by Tang and Zhang and its limiting solution. Fu and Phillips' diffus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Consequently, the value of mutual diffusion coefficients is strongly dependent on the composition and spatial resolution of such profiles, forcing many researchers to smooth composition profiles before analysing them. 1.25 Average value (SOR ¼ 20%) [10] Athabasca bitumen 295 17 AE 4 1 0 -90% by mass solvent [13] N-hexane bitumen: m ¼ 56.5 Pa s @ 295.15 K 296.15 AE 1.5 1.07 Solvent finite dilution [3] bitumen: m ¼ 56.5 Pa s @ 298.15 K 296.15 AE 1.5 0.086 Solvent finite dilution [16] Cold Lake: m ¼ 130 Pa s @ 298.15 K 303.15 83.2 Average value (SOR ¼ 20%) [9] heavy oil: m ¼ 12 Pa s @ 298.15 K 295.15 AE 2 35.2 Average value (SOR ¼ 72%) [12] Cold Lake: m ¼ 130 Pa s @ 298.15 K 303.15 (?) Incorporation of density changes in calculations of mutual diffusion coefficients appears to be of little importance with respect to concentration dependency.…”
Section: All Optical Methods For Measuring In Situ Concentrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, the value of mutual diffusion coefficients is strongly dependent on the composition and spatial resolution of such profiles, forcing many researchers to smooth composition profiles before analysing them. 1.25 Average value (SOR ¼ 20%) [10] Athabasca bitumen 295 17 AE 4 1 0 -90% by mass solvent [13] N-hexane bitumen: m ¼ 56.5 Pa s @ 295.15 K 296.15 AE 1.5 1.07 Solvent finite dilution [3] bitumen: m ¼ 56.5 Pa s @ 298.15 K 296.15 AE 1.5 0.086 Solvent finite dilution [16] Cold Lake: m ¼ 130 Pa s @ 298.15 K 303.15 83.2 Average value (SOR ¼ 20%) [9] heavy oil: m ¼ 12 Pa s @ 298.15 K 295.15 AE 2 35.2 Average value (SOR ¼ 72%) [12] Cold Lake: m ¼ 130 Pa s @ 298.15 K 303.15 (?) Incorporation of density changes in calculations of mutual diffusion coefficients appears to be of little importance with respect to concentration dependency.…”
Section: All Optical Methods For Measuring In Situ Concentrationmentioning
confidence: 99%
“…4. 1.62 Average value (SOR ¼ 20%) [10] heavy oil: m ¼ 6 Pa s @ 298.15 298.15 4-85 $0-80% by volume solvent [14] N-heptane bitumen: m ¼ 56.5 Pa s @ 295.15 K 296.15 AE 1.5 1.07 Solvent finite dilution [3] bitumen: m ¼ 56.5 Pa s @ 298.15 K 296.15 AE 1.5 0.086 Solvent finite dilution [16] Cold Lake: m ¼ 130 Pa s @ 298.15 K 303.15 83.2 Average value (SOR ¼ 20%) [19] heavy oil: m ¼ 12 Pa s @ 298.15 K 295.15 AE 2 35.2 Average value (SOR ¼ 72%) [12] Cold Lake: m ¼ 130 Pa s @ 298.15 K 303.15 (?) More accurately, at later diffusion times where density gradients are low, Equation (14) can be safely employed, provided that the gradients are experimentally detectable outside the error of measurement.…”
Section: All Optical Methods For Measuring In Situ Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…
Previous study [1][2][3] indicated that phenol transport from spilled bitumen into flowing aquifer was controlled by slow molecular diffusion of phenol in bitumen as the ratedetermining step. This simplified de-coupled transfer mechanism has led to a 2 dimensional planar flow analytical solution, which described the time-dependent phenol concentration in a flowing stream 4 .
…”
mentioning
confidence: 99%